Structural and ultrastructural characteristics of the tongue of the Collared Peccary (Pecari tajacu, Linnaeus, 1758) - Barbosa, Gabriela Klein [UNESP]; dos Santos Jacob, Carolina [UNESP]; Pimentel Neto, Jurandyr [UNESP]; de Oliveira, Moacir Franco; Rici, Rose Eli Grassi; Watanabe, Ii-Sei; Ciena, Adriano Polican [UNESP] (Wiley, 2020)
The tongue is an important organ in species due to its feeding functions, and its structure is influenced by the habitat and diet. The Collared Peccary (Pecari tajacu, Linnaeus, 1758) is a terrestrial mammal that is distributed on the American continents and has an omnivorous diet. This study aimed to describe the morphological characteristics of the tongue, lingual papillae and the connective tissue cores (CTCs) of the Collared Peccary. Eight tongues were collected from the Wild Animals Multiplication Center. The samples (n = 6) were processed for three-dimensional analysis of their dorsal epithelium, and their CTCs by scanning electron microscopy and the other samples (n = 2) were used to observe ultrastructural characteristics by transmission electron microscopy. Filiform papillae were observed in the lingual apex and body with their conical CTC demonstrating ripples in their extent. Two types of fungiform papillae were observed, the first in the apex and body with a dome-shaped CTC and the second forming a dorsolateral line with a radial pattern CTC. The vallate papillae were bilateral in the caudal region with the CTCs, characterised by numerous projections, and foliate papilla were not observed. We found a new type of papilla anteriorly to the vallate papilla with an irregular groove and a CTC formed by triangular-shaped projections with a duct opening at the top. We concluded that the lingual papillae of the Collared Peccary resemble those papillae of other mammals, however, were revealed another form of their CTCs and a new lingual papillae morphological description.
Keywords: electron microscopy; lingual papillae; morphology; tongue; ultrastructure